2001
DOI: 10.1104/pp.010264
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthetic Pathway of Insect Juvenile Hormone III in Cell Suspension Cultures of the Sedge Cyperus iria

Abstract: In most insect species, juvenile hormones regulate critical physiological processes such as metamorphosis and reproduction. In insects, these sesquiterpenoids are synthesized by retrocerebral endocrine organs, the corpora allata, via the classical mevalonate (MVA) pathway. One of these compounds, juvenile hormone III (JH III), has also been identified in the sedge Cyperus iria. In higher plants, biosynthesis of the sesquiterpenoid backbone may proceed through two distinct pathways: the MVA pathway or the 2C-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 41 publications
1
22
0
Order By: Relevance
“…Cultures of C. merolae were grown in the presence of three general inhibitors of P450 enzymes. Two of the inhibitors tested, clotrimazole and miconazole, at the relatively high concentrations used in these experiments (the concentrations used in this study were the same as used by Bede et al [4] for cell suspension cultures of the sedge Cyperus iria, except that ancymidol was used in the present study at a 3.3-fold-higher concentration), very quickly (within one day) killed and bleached cultures of C. merolae. In the presence of the third inhibitor tested, ancymidol, cultures of C. merolae continued to grow and divide at the same rate as control cultures (as measured by the optical density at 730 nm) for about two generations before a relatively sudden arrest of growth.…”
Section: This Work Phpketoskmentioning
confidence: 99%
“…Cultures of C. merolae were grown in the presence of three general inhibitors of P450 enzymes. Two of the inhibitors tested, clotrimazole and miconazole, at the relatively high concentrations used in these experiments (the concentrations used in this study were the same as used by Bede et al [4] for cell suspension cultures of the sedge Cyperus iria, except that ancymidol was used in the present study at a 3.3-fold-higher concentration), very quickly (within one day) killed and bleached cultures of C. merolae. In the presence of the third inhibitor tested, ancymidol, cultures of C. merolae continued to grow and divide at the same rate as control cultures (as measured by the optical density at 730 nm) for about two generations before a relatively sudden arrest of growth.…”
Section: This Work Phpketoskmentioning
confidence: 99%
“…It should be mentioned that the use of juvenile hormone (JH) or JH-based compounds for pest control was early suggested by some authors [15][16][17] as "third generation insecticides". Screening new targets involved in JH-biosynthesis within the corpora allata (CA), JH-producing organs in insects, has been a subject of study in the past four decades [18]. So, compounds that interact with JH, stimulate JHbiosynthesis, inhibit JH-biosynthesis or interfere with its catabolism can be utilized as new insecticides against insect pests [19].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the design of JH mimics or anti-JH agents is an effective strategy for insecticide discovery. Screening new targets involved in JH biosynthesis has been a subject of study for two decades (Bede et al, 2001). As HMGR has been postulated to be a key enzyme in the regulation of the MVA pathway in insects, some HMGR inhibitors (statins) have been used to investigate their effects on JH biosynthesis.…”
Section: Discussionmentioning
confidence: 99%